2007
DOI: 10.1002/scj.20260
|View full text |Cite
|
Sign up to set email alerts
|

An architecture of self‐organizing map for temporal signal processing and its application to a Braille recognition task

Abstract: SUMMARYA self-organizing map (SOM) performs a mapping of an object preserving its topological relations between input and output spaces, and also can be seen as a coordinate transformer that preserves adjacency relations. Since the standard SOM cannot deal with temporal data intrinsically, in this paper we provide new feedback pathways around the competitive layer to refer to context information of the past history. An extra output layer is added next to the competitive layer to represent secondary candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…First of all, a Braille recognition task was tried [5]. Even though only four kinds of city names were adopted, good performance on temporal signal processing for both temporal elasticity and spatial displacement was conårmed.…”
Section: Overview Of Preceding Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…First of all, a Braille recognition task was tried [5]. Even though only four kinds of city names were adopted, good performance on temporal signal processing for both temporal elasticity and spatial displacement was conårmed.…”
Section: Overview Of Preceding Studiesmentioning
confidence: 99%
“…Following to the above-mentioned trend in temporal signal processing by SOM architecture, an Elman-type feedback SOM (EFSOM) was proposed [5]. It was applied to various kinds of tasks, including a Braille recognition task [5], an on-line character recognition task [6], [7] and so on, and it showed good performance on temporal signal processing for both temporal elasticity and spatial displacement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies that neural networks was applied to Braille recognition have been reported. In [2], Braille documents read by tactile were considered as time series information, and a new SOM architecture with feedback connections was proposed. In [3], hierarchical neural network has been applied to Japanese Braille transcription, and its accuracy was improved.…”
Section: Introductionmentioning
confidence: 99%
“…CNN has some remarkable features:(1) CNN can be arranged in matrix and implemented by a simple analog circuit called a cell. (2) Each cell in CNN is connected to its neighbors only. Hence, its computation efficiency is superior to that of fullconnected neural network such as Hopfield model.…”
Section: Introductionmentioning
confidence: 99%